Short-term prognosis of polypharmacy in elderly patients treated in emergency departments: results from the EDEN project - Jesus Ruiz Ramos; Aitor Alquézar-Arbé; Ana Juanes Borrego; Guillermo Burillo Putze; Sira Aguiló; Javier Jacob; Cesáreo Fernández; Pere Llorens; Francisco de Borja Quero Espinosa; Susana Gordo Remartinez; Rocio Hernando González; Miguel Moreno Martín; et al. (SAGE Publishing, 2024)
Background: Polypharmacy is a growing phenomenon among elderly individuals. However, there is little information about the frequency of polypharmacy among the elderly population treated in emergency departments (EDs) and its prognostic effect. This study aims to determine the prevalence and short-term prognostic effect of polypharmacy in elderly patients treated in EDs. Methods: A retrospective analysis of the Emergency Department Elderly in Needs (EDEN) project's cohort was performed. This registry included all elderly patients who attended 52 Spanish EDs for any condition. Mild and severe polypharmacy was defined as the use of 5-9 drugs and ⩾10 drugs, respectively. The assessed outcomes were ED revisits, hospital readmissions, and mortality 30 days after discharge. Crude and adjusted logistic regression analyses, including the patient's comorbidities, were performed. Results: A total of 25,557 patients were evaluated [mean age: 78 (IQR: 71-84) years]; 10,534 (41.2%) and 5678 (22.2%) patients presented with mild and severe polypharmacy, respectively. In the adjusted analysis, mild polypharmacy and severe polypharmacy were associated with an increase in ED revisits [odds ratio (OR) 1.13 (95% confidence interval (CI): 1.04-1.23) and 1.38 (95% CI: 1.24-1.51)] and hospital readmissions [OR 1.18 (95% CI: 1.04-1.35) and 1.36 (95% CI: 1.16-1.60)], respectively, compared to non-polypharmacy. Mild and severe polypharmacy were not associated with increased 30-day mortality [OR 1.05 (95% CI: 0.89-2.26) and OR 0.89 (95% CI: 0.72-1.12)], respectively. Conclusion: Polypharmacy was common among the elderly treated in EDs and associated with increased risks of ED revisits and hospital readmissions ⩽30 days but not with an increased risk of 30-day mortality. Patients with polypharmacy had a higher risk of ED revisits and hospital readmissions ⩽30 days after discharge.